Risk of malignancy index 4 for differentiating benign from malignant ovarian tumor - Chandni; Kumar Bind, Nirbhay (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Approximately 22% of gynaecologic cancers are of ovarian origin, but 47% of all gynaecologic cancer deaths occur in women who have ovarian cancer. Ovarian cancer is usually diagnosed at an advanced stage because most of the symptoms are nonspecific, hence, the difficulty in diagnosis at early stages. In general, there is no effective screening test for ovarian cancer. Aim was to evaluate the ability of risk of malignancy index 4 (ROMI 4) to differentiate benign from malignant ovarian tumors. Methods: A prospective observational study was conducted in April 2019 to march 2020. Results: In the present study the ROMI 4 score at cut-off ≥ 450 had sensitivity, specificity, PPV and NPV of 74.3%, 65.3%, 42.6% and 88% respectively for malignant ovarian tumor. Conclusions: Preoperative ROMI 4 score ≥450 will lead to rational basis for further referral to higher centre or gynaecology oncologist timely for appropriate surgical intervention/ management.